Cardiopulmonary Resuscitation and real life - Carolina Prevaldi (Emergency Care Journal, 2006)
The Guidelines for Cardiopulmonary Resuscitation (CPR) and Emergency Cardiovascular Beloveds are, probably, the most well known and widely-read guidelines in Medicine. Although for decades these guidelines are regularly revisited every 5 years, the survival to cardiac arrest on the territory remain unsatisfactory, attesting itself on 6,4% or less. These discouraging outcomes caused some reflections on the validity of the guidelines concrete application. Some reviews, supported by the results of some good studies recently published, and the introduction of new technologies have produced remarkable changes not only in the guidelines, but also in the methodology subtended to the review process, and the consequent creation of new recommendations. The recent publication on Circulation of the 2005 guidelines is the standing point for an analysis of the great changes carried out.